2021
DOI: 10.18488/journal.31.2021.82.173.183
|View full text |Cite
|
Sign up to set email alerts
|

Visitor Comments about Botanic Parks and Gardens in the Context of Botanical Tourism

Abstract: Botanical parks and gardens present different natural beauties together and allow the recognition of flora varieties. Within the scope of botanical tourism, botanical parks and gardens constitute one of the important visiting points of tourists. In this study, visitor comments on botanical parks / gardens are analyzed. Qualitative research method was used in the study. The study data consists of visitor comments on TripAdvisor website for "Ankara Botanical Park", "Atatürk Botanical Park", "Gaziantep Botanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…They are increasingly integrating with other urban green areas [25,11], allowing visitors to connect with nature and explore plant diversity in a peaceful, immersive environment. Additionally, botanical gardens significantly promote ecotourism and sustainable tourism practices, highlighting their importance today [26,27]. These gardens cater to various visitor motivations, including stress relief and social interaction, as demonstrated by research conducted on American gardens, which observed therapeutic effects [28,29,30,31].…”
Section: Evolution and Impacts Of Botanical Gardensmentioning
confidence: 99%
“…They are increasingly integrating with other urban green areas [25,11], allowing visitors to connect with nature and explore plant diversity in a peaceful, immersive environment. Additionally, botanical gardens significantly promote ecotourism and sustainable tourism practices, highlighting their importance today [26,27]. These gardens cater to various visitor motivations, including stress relief and social interaction, as demonstrated by research conducted on American gardens, which observed therapeutic effects [28,29,30,31].…”
Section: Evolution and Impacts Of Botanical Gardensmentioning
confidence: 99%